2019
DOI: 10.1111/jocd.13218
|View full text |Cite
|
Sign up to set email alerts
|

“A Multi‐center, randomized, double blinded, comparative study of two hyaluronic acid fillers for temporary restoration of mid‐face volume in Asians”

Abstract: Background There have been few studies using hyaluronic acid fillers to restore mid‐face volume deficit especially in Asians. Aims This study compared the efficacy and safety of two highly cohesive hyaluronic acid fillers, Neuramis® Volume Lidocaine and Juvederm® Voluma® with Lidocaine (VYC‐20L), for temporary restoration of mid‐face volume in Asians. Patients/Methods A total of 88 subjects with moderate to severe age‐related mid‐face volume deficit on the Mid‐Face Volume Deficit Scale (MFVDS) received Neurami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
(48 reference statements)
2
9
1
Order By: Relevance
“…In our original 24-week study, both fillers showed similar effectiveness and safety profile for temporary restoration of mid-face volume in Asians. 13 In this study, the responder rates based on MFVDS in the mid-face 48 weeks after the final treatment were 81.93% and 80.72% for SHAPE-NVL and VYC-20L, respectively. These rates were slightly lower than those in previous studies with VYC-20L, which reported a responder rate of 85.2% 48 weeks after treatment.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…In our original 24-week study, both fillers showed similar effectiveness and safety profile for temporary restoration of mid-face volume in Asians. 13 In this study, the responder rates based on MFVDS in the mid-face 48 weeks after the final treatment were 81.93% and 80.72% for SHAPE-NVL and VYC-20L, respectively. These rates were slightly lower than those in previous studies with VYC-20L, which reported a responder rate of 85.2% 48 weeks after treatment.…”
Section: Discussionmentioning
confidence: 58%
“…The MFVDS assesses the degree of MVD and validated by previous studies. 5,7,13 Subjects who had recently received anticoagulant therapy or antiplatelet therapy (within 10 days) or were hypersensitive to HA or local anesthetics, were excluded. Subjects with asymmetric MVD, history of facial procedures such as plastic surgery, tissue grafting, tissue augmentation using hydroxyethylmethacrylate, dextran, or polylatic acid, or facial scar interfering with accurate assessment by the investigator were also excluded.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations